Preliminary design and validation of a Real Time model for hardware in the loop testing of bypass valve actuation system. (1st March 2015) - Pugi, Luca; Galardi, Emanuele; Carcasci, Carlo; Rindi, Andrea; Lucchesi, Nicola
Highlights: A Real Time Model of a turbine bypass system is presented and validated. An Hardware in the Loop rig is used for calibration of positioneers and turbine bypass regulators. Testing activities on the proposed test rig, confirm the feasibility of the proposed approach. Abstract: During the start-up and shut-down phases of steam power plants many components are subjected to pressure and temperature transients that have to be carefully regulated both for safety and reliability reasons. For this reason, there is a growing interest in the optimization of turbine bypass controllers and actuators which are mainly used to regulate the plant during this kind of operations. In this work, a numerically efficient model for Real Time (RT) simulation of a steam plant is presented. In particular, a modular Simulink™ library of components such as valves, turbines and heaters has been developed. In this way it is possible to easily assemble and customize models able to simulate different plants and operating scenarios. The code, which is implemented for a fixed, discrete step solver, can be easily compiled for a RT target (such as a Texas Instrument DSP) in order to be executed in Real Time on a low cost industrial hardware. The proposed model has been used for quite innovative applications such as the development of a Hardware In the Loop (HIL) test rig of turbine bypass controllers and valve positioners. Preliminary experimental activities and results of the proposed test rig developed for Velan ABV are introduced and discussed.